MAIN PROVISIONS OF THE QUALITY CONCEPT PERSON-ORIENTED EDUCATION - Е.V. Bondarivska (Academy of Cognitive and Natural Sciences, 2004)
The article deals with the problems of personality-oriented education as well as the possibility of realization of the main criterion of quality of education.